Sensibilidad antifúngica en levaduras del género Malassezia spp. ¿Qué sabemos acerca de este tema? (2021)
Malassezia genus is a lipid dependent basidiomycetous yeast present in the normal cutaneous microbiota of homeothermic animals associated with diseases. This study aims to review different methodologies implemented for the analysis of antifungal susceptibility in Malassezia spp. We follow a search in the databases PUBMED, MEDLINE, SCOPUS, using the terms: Malassezia antifungal susceptibility. Therefore, we included 25 papers for analysis. As a result, these studies show that Malassezia yeasts are generally susceptible to azole compounds, except for fluconazole. Furthermore, these yeasts show resistance to compounds of the echinocandin class. Finally, we found low agreement and low reproducibility between the results and the methodologies used in the studies, which were, broth microdilution method, agar disk diffusion method and Etest method.